Thermodynamic, thermoeconomic, and exergoeconomic analysis of a UAV two stroke engine fueled with gasoline-octanol and gasoline-hexanol blends - Özer, Salih; Tuncer, Erdal; Demir, Usame; Gulcan, Halil Erdi (Pergamon-Elsevier Science Ltd, 2025)
In recent years, as the use of Unmanned Aerial Vehicle (UAV) engines has increased in various application areas such as military fields, defense, emergencies, and mapping, the use of these engines with fossil-based fuels has raised environmental concerns. The addition of heavy alcohols such as octanol and hexanol, which have high energy densities, to the fossil-based fuels used may help reduce environmental concerns and contribute to performance improvement. In this study, the performance, emissions, thermodynamic, thermoeconomic, and exergoeconomic analysis of a two-stroke engine operating with gasoline-octanol and gasoline-hexanol fuels in a UAV is conducted. There are no studies in the literature that examine the energy, exergy, thermoeconomic, and exergoeconomic aspects of a two-stroke UAV engine operating with gasoline-octanol and gasoline-hexanol fuel mixtures. The aim of this study is to understand the performance and emission characteristics of used heavy alcohols such as octanol and hexanol in a two-stroke UAV engine, and to examine them from a thermodynamic perspective. The experiments are carried out at different shaft speed ranges (3250, 3750, 4500, 5250, and 6250 rpm). Additionally, seven different fuels are used in the experiments: gasoline, gasoline-octanol mixtures (volumetrically 10 %, 20 %, and 30 %), and gasoline-hexanol mixtures (volumetrically 10 %, 20 %, and 30 %). The results show that increasing the octanol content in gasoline to 30 % (OC30) reduces the specific fuel consumption (SFC) by up to 5.5 % (at 6250 shaft speed), while increasing the hexanol content to 30 % (HX30) increases it by 6 % (at 5250 shaft speed). CO emissions decrease by an average of 5.3 % and 9.2 % with OC30 and HX30 fuels, respectively (both at 6250 shaft speed), while CO2 emissions increase by an average of 3 % and 10 % with OC30 and HX30 fuels, respectively. With OC30 fuel, the exergetic destruction decreases by an average of 6 % compared to gasoline, while with HX30 fuel, it increases by an average of 3.3 %. OC30 increases the exergetic efficiency by an average of 5.4 % compared to gasoline, whereas HX30 decreases it by 2.9 %.
Keywords: Energy and exergy analysis; Exergoeconomic; Hexanol; Octanol; Thermoeconomic; Two stroke engine